Reliable screening of beta2‐adrenoceptor ligands from Rheum palmatum L extract using a paper‐based chromatographic column containing the immobilized receptor. Issue 1 (1st December 2021) - Xiong, Xunyu; Nan, Yefei; Yu, Hongjiang
Abstract: Isolation and identification of bioactive compounds from complex matrices like traditional Chinese medicines still challengeable because of the low specificity, efficiency and high false positive rate in the current screening methods. Herein, we reported a method for screening ligands of beta2 ‐adrenoceptor from Rheum palmatum L extract. The method involved in immobilization of beta2 ‐adrenoceptor on a paper material of polytetrafluoroethylene membrane by a site‐specific covalent method, characterization of the immobilized receptor by X ray photoelectron spectroscopy and fourier transform infrared spectroscopy, parallel screening of Rheum palmatum L extract by immobilized beta2 ‐adrenoceptor column and the control column, identification of the screened compounds by mass spectrometry and the binding mechanism analysis of the screened compounds with beta2 ‐adrenoceptor by molecular docking. Morphological analysis showed beta2 ‐adrenoceptor was successfully immobilized. Aloe‐emodin, rhein, emodin, chrysophanol, and physcion were screened as the potential bioactive compounds binding to the receptor from Rheum palmatum L extract. Van der Waals force and π‐π stacking interactions were the main driving forces for these compounds to bind with the receptor. These results indicated that paper‐based receptor chromatography with a peak‐missing strategy is reliable in screening and identifying bioactive compounds within medicinal plants that bind to G protein coupled receptors.